On Retention of Eventual Stability of Perturbed Impulsive Differential Systems - Sood, Anju; Srivastava, Sanjay Kumar (Journal of Mathematical and Fundamental Sciences, 2016)
In this paper, a system of non nonlinear differential equations with impulse effect at fixed time moments is considered and criteria for retention of uniform eventual stability of its perturbed impulsive differential systems under vanishing perturbations are established. Sufficient conditions are obtained by using piecewise continuous Lyapunov functions. An example is also worked out to illustrate the results. AMS Subject Classification: 34CXX, 34DXX, 34A37, 34K45.